Realization of the Logistic Approach in the International Cargo Delivery System - Victor Aulin; Oleg Lyashuk; Olexiy Pavlenko; Denis Velykodnyi; Andrii Hrynkiv; Sergii Lysenko; Dmytro Holub; Yuriy Vovk; Volodymyr Dzyura; Mariana Sokol (Communications - Scientific letters of the University of Zilina, 2019)
Fierce rivalry in the transport market raises serious reassessment and implementation of new approaches to logistics companies and trade enterprises in marketing of goods. To maintain the volume of domestic sales and output to the external one, producers and trading firms are forced to expand their trade and economic relations that occur in other regions. The integration of the world economy and policy orientation of foreign trade to free trade greatly simplify the task of setting up the free trade and economic connections, but the question is how quickly and efficiently, with the least costs, it is necessary to put the goods in the right region to the customer.In modern market conditions, international container transportation of goods between Ukraine and the European Union countries has a prospect of development, as each year the number of orders in transport and logistics enterprises increases. After analyzing the status of orders, the problem has been detected and widely connected with the method of organization of container cargo delivery in international communication and the formation of rational technology of serviced. To solve this problem a method of logistic approach to the system of containers transportation has been proposed based on the cybernetic model „white box“. The initial stage of its implementation involves formation of the limitation system of input parameters and factors that are consistent with the needs of the customer firm and the company performing transportation. Ten alternative order services schemes, each of which takes into account the possible combinations of operations, has been proposed.Based on the company „Inter Trans Logistic“, which serviced the order of the company „Agricultural Holding August“ for the transportation of rape seeds, 10 tons of corn on demand and a portion of sunflower oil 20,000 liters, according to their applications for transportation, a logistic approach using a cybernetic model „white box“ has been implemented. Based on the mathematical models of changes in the total costs of the international container cargo shipping company of the customer, it has been shown that the maximum expenses are occurring in the implementation of the scheme 1 service order. In that case, the costs have been in the range of 848.72 to 7455.41 US $, according to a certain series of experiments. Based on the condition of the minimum cost function for container transportation, scheme 1 has been chosen as limiting scheme of service order against which the assessment carried out changes of the total costs in the implementation of other schemes. In percentage display according to Scheme 1, the following percentage intervals have been deducted for the reduction of sales costs: Scheme 2 - 12.70 to 34.98%; Scheme 3 - 2.93 to 12.00%; Scheme 4 - 2.06 to 10.88%; Scheme 5 - 1.69 to 4.25%; Scheme 6 - 0.87 to 3.28%; scheme7 - 0.97 to 2.58%; Scheme 8 - 1.64 to 4.45%; Scheme 9 - 2.66 to 11.77%; scheme 10 - 2.33 to 9.94%.The results of experimental studies indicate that when the proposed methodology of the logistic approach, using the „white box“ based on the company „Inter Trans Logistic“ to international container transportation of goods in relation to the application of the company „Agricultural Holding August“ for transportation, the scheme 2 sequence of transport operations has been effective. In its realization the costs for 12.70 to 34.98% has been decreased in comparison with the marginal service scheme.